Differences in sensory nerve block between levobupivacaine and bupivacaine at low concentrations in humans and animals - Akiyuki Sakamoto; Satoshi Tanaka; Takashi Ishida; Mikito Kawamata (PLoS ONE, 2025)
Physiochemical properties of levobupivacaine and bupivacaine are identical, but pharmacokinetic and pharmacodynamics properties differ due to stereoselective interactions at the molecular sites of action. An evaluation of nerve block characteristics is essential for optimal clinical application. This study compared the sensory blocking characteristics of levobupivacaine to bupivacaine in humans and model animals. Levobupivacaine and bupivacaine were compared for sensory block efficacy using a randomized, double-blinded, crossover study design. Eighteen healthy volunteers were randomized to receive levobupivacaine or bupivacaine by subcutaneous injection into the forearm, followed by the other drug 1 week later with injection order counterbalanced across subjects. Tactile detection and mechanical pain thresholds were determined using von Frey hairs and thermal pain threshold using a thermal stimulator. Effects of levobupivacaine and bupivacaine, on the spiking activity of spinal dorsal horn (SDH) neurons evoked by innocuous or noxious stimuli were also compared in anesthetized Sprague–Dawley rats by in vivo extracellular recordings. There were no significant differences in mechanical and thermal pain thresholds following levobupivacaine or bupivacaine injection at 0.025%, 0.0625%, and 0.125%. There was also no significant difference in tactile detection threshold following levobupivacaine or bupivacaine injection at 0.125%. However, tactile detection threshold was significantly higher after administration of bupivacaine at 0.025% and 0.0625% compared to equivalent doses of levobupivacaine. Subcutaneous injection of bupivacaine at 0.05% also induced significantly greater inhibition of SDH neuron spiking activity evoked by innocuous stimuli compared to an equivalent dose of levobupivacaine, while there was no significant difference in suppression of spiking activity evoked by noxious stimuli. Low-dose bupivacaine induces greater suppression tactile sensation than low-dose levobupivacaine. Thus, low-dose levobupivacaine demonstrates relatively greater blocking selectivity for noxious over innocuous stimuli compared to low-dose bupivacaine. Levobupivacaine may be advantageous for applications where pain must be suppressed but non-nociceptive sensations maintained.